Filling the Empty Space: Women and Latin American Theatre - Kirsten F. Nigro (Studies in 20th & 21st Century Literature, 1996)
In recent years, Latin American women have begun to appropriate and fill a space once empty of their presence. This essay looks at the work of four such women, (Diana Raznovich and Cristina Escofet of Argentina, Raquel Araujo of Mexico and the Peruvian Sara Joffre), to see how they give substance and voice to their particular concerns. In the process, this essay focusses on: 1) the notion of gender as performance; 2) the feminist deconstruction of narrative; 3) the female body in theatrical space; and 4) new, postmodern ways of doing feminist political theatre.
Keywords: Latin American women; women; space; Diana Raznovich; Cristina Escofet; Raquel Araujo; Sara Joffre; voice; gender; performance; feminist deconstruction; narrative; female body; theatrical space; theatre; postmodernism; feminist political theatre